Antipsychotic Switching in Bipolar Disorder with Metabolic Comorbidities: A Case Report - Syadza, Lailatus; Ahadiah, Hayyunah Rohmatul; Shafly, Moch. Syafirul Nur; Algristian, Hafid; Huda, Miftakhul (Yayasan Sinergi Kawula Muda, 2025)
Bipolar disorder is a chronic psychiatric condition marked by alternating episodes of mania, hypomania, and depression, often with psychotic features. Treatment resistance and adverse metabolic effects from long-term antipsychotic use pose significant challenges. This case report presents a 31-year-old male in Indonesia with bipolar disorder and metabolic comorbidities, including type 2 diabetes mellitus and dyslipidemia. Initially treated with clozapine, the patient experienced metabolic decompensation, prompting an urgent switch to quetiapine. Post-switch, he exhibited improved mood stability and remission of psychotic symptoms, though residual depressive symptoms persisted. Lithium and sertraline were introduced to address these, with careful monitoring. The case highlights the importance of individualized switching strategies in bipolar disorder, particularly in patients with metabolic risks. Antipsychotic selection should consider both psychiatric efficacy and metabolic safety. Despite pharmacological improvement, functional recovery was incomplete, emphasizing the role of psychosocial interventions and culturally informed care. The integration of religious values and family support proved essential in this context. Although effective in symptom stabilization, the switch strategy remains limited by the lack of long-term follow-up and generalizability. This report underscores the need for structured protocols for antipsychotic switching and holistic treatment models, especially in resource-limited settings. Future research should explore integrative approaches that address both psychiatric and physical health dimensions, ensuring continuity of care beyond pharmacological intervention.